Pendidikan Moderasi Beragama dalam Penanaman Sikap Kerukunan antar Siswa di SMAN 8 Kota Malang - Elsyam, Sulthan Fathani; Rossidy, Imron (ISLAMIKA, 2024)
A nation develops because of the regeneration that is born through the process of education and learning. The next generation is guaranteed protection and respect for religious rights according to their respective teachings. Although, there are still some cases that tarnish the orientation of students in pursuing education so that it affects the development of science. This discussion aims to examine the strategy, process, and evaluation of religious moderation education in cultivating harmony among students at SMAN 8 Malang City. The researcher used a qualitative approach of field study type that collected data through participant observation, interviews, and documentation. The data collection was then classified and analyzed before finally the data was presented with conclusions. The data and research results indicate that various strategies are applied through in-school activities, project-based activities (P5), and student character empowerment. As for the implementation process, researchers describe it with various points including, 1) exemplary, 2) instilling discipline, 3) creating a conducive atmosphere, and 4) integration and internalization of character values. Meanwhile, the evaluation of its implementation consists of inhibiting factors, namely the lack of harmony by some students. However, this factor can be covered by the existence of supporting factors which are evaluated directly by the teacher by supervising and reprimanding them.